Dataset 1: Robust measurement of flexoelectro-optic switching with different surface alignments - O'Neill, J; Fells, J; Welch, C; Mehl, G; Yip, C; Wilkinson, T; Booth, M; Elston, S; Morris, S (University of Oxford, 2019)
All data was taken and processed in MATLAB The alignment of chiral nematic liquid crystals in the so-called uniform lying helix geometry allows for the observation and exploitation of the flexoelectro-optic effect. However, high-quality uniform lying helix alignment is difficult to achieve reliably, and this can potentially impact the accuracy of the measurements made on the flexoelectro-optic switching behaviour. Here we show that, using an appropriate method, it is possible to make measurements of the flexo-electric coefficients which are not substantially influenced by the alignment quality.